IMPROVING CRITICAL THINKING SKILLS IN A THREE-VARIABLE LINEAR EQUATION SYSTEM THROUGH A PROBLEM BASED LEARNING MODEL IN CLASS X MA NURUL ULUM - Hamidah, Nuria Fitrian; Rizki Pradita, Diyah Ayu; Asy’ari, Dian Noer (Journal on Research and Review of Educational Innovation, 2023)
The critical thinking ability of students who are classified as low is a trigger for teachers to be required to be smart in choosing the learning model to be used. Problem Based Learning is a learning model that is able to develop students' critical thinking skills using problems as their starting point. The purpose of this study was to determine the effect of using the Problem Based Learning model on increasing students' critical thinking skills in solving SPLTV questions. This research used the Quasi Experimental design experimental research method and was carried out in May 2022, class X MA Nurul Ulum, Mertak Tombok, NTB. Data collection techniques used are observation, documentation, interviews, and tests. Data analysis used the Normality Test, Homogeneity Test and Hypothesis Test which were calculated using SPSS 16 for Windows. The results showed that learning with the Problem Based Learning model experienced an increase in critical thinking skills with an average value of 31,87 to 76,25 with the results of the hypothesis test showing the results of 7,401 > 2,021 or which means that the Problem Based learning model Learning can improve students' critical thinking skills.